1996
DOI: 10.1074/jbc.271.32.19489
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillin-1 and Fibulin-2 Interact and Are Colocalized in Some Tissues

Abstract: Microfibrils 10 -12 nm in diameter are found in elastic and non-elastic tissues with fibrillin as a major component. Little is known about the supramolecular structure of these microfibrils and the protein interactions it is based on. To identify protein binding ligands of fibrillin-1, we tested binding of recombinant fibrillin-1 peptides to different extracellular matrix proteins in solid phase assays. Among the proteins tested, only fibulin-2 showed significant binding to rF11, the N-terminal half of fibrill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
214
0
4

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 206 publications
(227 citation statements)
references
References 44 publications
9
214
0
4
Order By: Relevance
“…Cells were washed with Tris buffered saline (TBS; 50 mM Tris [pH 8.0], 150 mM NaCl) and then incubated with rabbit antifibrillin antibody (pAb9543; kindly provided by Dr. Lynn Sakai [17,24]) at 1:250 dilution in TBS for 2 hours at 37°C. This antibody was raised against the amino-terminal half of human fibrillin-1 and cross-reacts with mouse fibrillin-1, but not with fibrillin-2 (17,24). Some cells were also incubated with mouse monoclonal anti-␣-smooth muscle actin (anti-␣-SMA) antibodies (clone 1A4; Sigma, St. Louis, MO) at a 1:250 dilution in TBS during the same time period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were washed with Tris buffered saline (TBS; 50 mM Tris [pH 8.0], 150 mM NaCl) and then incubated with rabbit antifibrillin antibody (pAb9543; kindly provided by Dr. Lynn Sakai [17,24]) at 1:250 dilution in TBS for 2 hours at 37°C. This antibody was raised against the amino-terminal half of human fibrillin-1 and cross-reacts with mouse fibrillin-1, but not with fibrillin-2 (17,24). Some cells were also incubated with mouse monoclonal anti-␣-smooth muscle actin (anti-␣-SMA) antibodies (clone 1A4; Sigma, St. Louis, MO) at a 1:250 dilution in TBS during the same time period.…”
Section: Methodsmentioning
confidence: 99%
“…Fibrillin-containing microfibrils interact both with basement membranes and with nearby elastic fibers and may help stabilize the extracellular matrix by forming a scaffold (17).…”
mentioning
confidence: 99%
“…Whilst the supra-molecular conformation of fibrillin within the microfibril remains a matter of debate, with published experimental evidence favouring both 1/3 staggered (Downing et al 1996;Lee et al 2004) and hinged arrangements (Baldock et al 2001;Kielty et al 2005), it appears clear that, in the mature microfibril, an average of eight processed monomers are present within each repeat (Baldock et al 2001;Sherratt et al 1997). It is likely that interactions of fibrillin-1 with itself and with MAGP-1, tropoelastin and fibulin-2, as demonstrated in vitro, play a central role in elastogenesis and elastic fibre function in vivo (Jensen et al 2001;Kielty et al 2005;Reinhardt et al 1996;Rock et al 2004;Tiedemann et al 2001). In addition to mediating matrix/matrix interactions, a Assembly of fibrillin into microfibrils and the association of microfibrils with tropoelastin to form elastic fibres is a highly organised process which is limited to foetal and early neonatal development.…”
Section: Structure and Functionmentioning
confidence: 99%
“…As with the LTBPs, their structure is based in contiguous cbEGF domains and three of the five fibulins (fibulin-1, -2 and -5) are known to be elastic fibre components (Kielty et al 2002). Fibulin-1 is primarily localised to the elastin core (Kostka et al 2001) whilst fibulin-2 and -5 are located at the microfibril/elastin interface (Nakamura et al 2002;Reinhardt et al 1996).…”
Section: Structure and Functionmentioning
confidence: 99%
“…This might be especially important for papillary carcinoma which exhibits a high degree of elastosis, 17 inasmuch as fibrillin-1 has been suggested to be colocalized with elastin in various tissues. 8,18 Although the mechanism of fibrillin-1 deposition in ECM is largely unknown, it has been shown that in epithelial cells, soluble heparin competitively inhibits an unknown interaction that is needed for ECM deposition of both fibrillin-1 and -2. 13 Moreover, a human fibrillin-1 mutation (Arg 2726 -Trp) which prevents proteolytic processing of the C-terminal domain, has been reported to result in impaired deposition of the product of the affected allele.…”
Section: Discussionmentioning
confidence: 99%